Analisis pengaruh fear of missing out pada penggunaan media sosial terhadap akhlak siswa di MAN 1 Kota Bogor - Fadhillah, Fajri (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
On the other hand, the use of social media in some cases has quite an impact on students' academic fields where they will experience a decrease in concentration in learning activities in class. One of the impacts that students will experience when using social media is Fear of Missing Out (FoMO). FoMO is a worry experienced by someone when other people are doing activities that are more enjoyable than or without them. The influence of social media at this time can also change the morals of today's students. This research aims to identify the influence of FOMO among social media users on student morals at MAN 1 Bogor City. In this research, the author chose descriptive research with the aim of explaining the influence of Fear of Missing Out on the use of social media on student morals. The qualitative approach aims to understand a phenomenon about what is experienced by the research subject, for example behavior, perceptions, interests, motivation, actions, by describing it through words, language and accurate information appropriate to the field. The research results show that students are currently affected by FOMO on social media which results in despicable and praiseworthy morals and teachers also have an important role in supervising their students' activities on social media and can educate students to be wise and responsible in using social media. The advice in this research is for students to be careful when using social media and for teachers to always supervise their students on social media. Abstrak Pada sisi lain penggunaan sosial media dalam beberapa kasus cukup berpengaruh pada bidang akademik siswa di mana mereka akan mengalami penurunan konsentrasi dalam kegiatan pembelajaran di kelas. Salah satu dampak yang akan dialami siswa pada penggunaan sosial media yaitu Fear Of Missing Out (FoMO). FoMO merupakan kekhawatiran yang dialami seseorang yang di mana orang lain sedang melakukan aktivitas yang lebih menyenangkan dari pada atau tanpa dirinya. Pengaruh sosial media pada saat ini juga dapat mengubah akhlak pada siswa pada saat ini. Penelitian ini bertujuan untuk mengidentifikasi pengaruhnya FOMO pada pengguna media sosial terhadap akhlak siswa di MAN 1 Kota Bogor. Dalam penelitian ini penulis memilih jenis penelitian deskriptif dengan tujuan menjelaskan terkait pengaruh Fear Of Missing Out pada penggunaan sosial media terhadap akhlak siswa. Pendekatan kualitatif bermaksud untuk memahami suatu fenomena tentang apa yang dialami oleh subjek penelitian misalnya perilaku, persepsi, minat, motivasi, tindakan, dengan mendeskripsi melalui kata-kata, bahasa dan informasi akurat sesuai di lapangan. Hasil penelitian menunjukkan bahwa siswa pada saat ini terdampak FOMO pada sosial media yang menghasilkan akhlak tercela dan terpuji dan guru juga memiliki peran penting dalam mengawasi kegiatan siswanya di media sosial serta dapat mengedukasikan siswa agar bijak dan bertanggung jawab dalam menggunakan sosial media. Saran dalam penelitian ini untuk siswa agar berhati-hati dalam bersosial media dan untuk guru agar selalu mengawasi siswanya di sosial media.